Response of squids to colours and intensities’ artificial light - Ibrahim, Sakri ’; Hajisamae, Sukree (Malaysian Journal of Science, 1999)
A study on the response of big fin reef squid (Sepioteuthis lessoniana) and mitre squid (Loligo chinensis) to different characteristics of artificial light was conducted in an experimental cage. The response of squids to lights was determined by the Average Mean Displacement Position. The two species responded significantly differently to intensities but not to colours of the light. Sepioteuthis lessoniana preferred a range of underwater illuminance of 1.5-25.0 lux whereas Loligo chinensis preferred a range of 1.5 - 22.5 lux. However, a peak range for both species was recorded at 2.5 - 10.0 lux. Sepioteuthis lessoniana showed a stronger positive phototactic behavior than Loligo chinensis. This study provides the knowledge on the behavioral response of squid to artificial light, and it may be useful to multi-species and species-selective harvesting techniques.